ANALISIS PENGARUH MINAT PEMANFAATAN DAN PENGGUNAAN SISTEM INFORMASI TERHADAP KINERJA INDIVIDU DENGAN MENGGUNAKAN UTAUT MODEL (Studi pada PT. Pertamina (persero) UPms IV) - Sekarini, Yunita Ayu; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2014)
Technological developments from the impact of globalization is so rapid now accompanied with the development of technology-based information systems. Along with the development of information technology, every organization now considers that the information system is essential to the survival of the company..The purpose of this study is to obtain empirical evidence of the influence performance expectation, effort expectancy, social influence to intention of Information System partially. The study population was all employees of PT. Pertamina (Persero) UPMS IV, while the sample 149 respondents drawn by purposive sampling technique. Type of data used primary data collection using questionnaire method.In this research, there were six hypotheses that have been processed using the Partial Least Square (PLS). Consists of three accepted hypothesis that a positive relationship between social influences on interest in the use of Information System, the conditions that facilitate the use of Information System and usage Information System on individual performance. Three hypotheses were rejected while the absence of a positive relationship between effort expectancy with intention of Information System, expectations of the business with the intention of Information System and intention of Information System on the use of Information System